Brad's status [videorecording (DVD)] - White, Mike, 1970-; Stiller, Ben, 1965-; Abrams, Austin, 1996-; Fischer, Jenna, 1974-; Wilson, Luke, 1971- (Universal Pictures Home Entertainment, 2018)
A father takes his son to tour colleges on the East Coast and meets up with an old friend who makes him feel inferior about his life's choices.